Properties of Car-Embedded Vibrating Type Piezoelectric Harvesting System - Bo-Gun Koo; Dong-Jin Shin; Dong-Hwan Lim; Min-Soo Kim; In-Sung Kim; Soon-Jong Jeong (Applied Sciences, 2021)
We investigated the harvesting performance of a double piezoelectric generator, which was embedded into the engine block of a small passenger car. The resonance frequency is approximately between 37 and 52 Hz, where the cantilever showed maximum displacement. In reality, the cantilever has a vibrating characteristic, which dramatically reduces displacement, even when the operating frequency deviates slightly from the resonance frequency. To acquire a large mechanical energy-to-electrical energy conversion, a multiple-piezoelectric generator was employed to absorb the energy even when the vibration switched from a resonance to a non-resonance frequency. In this study, a variable mass box was designed and installed in the engine block of a car. The variable mass box consisted of the serial connection of two masses with different weights. The operating frequency deviated from a resonance to a non-resonance frequency within a few hertz (3~4 Hz); the reduction in vibration was lower, leading to a significant acquisition of the resulting power. This is due to the variable matching of the generator, realized by the action of dual mass. This type of generator was installed in the engine block and produced up to 0.038 and 0.357 mW when the engine was operating at 2200 and 3200 rpm, respectively.